The I quit sugar cookbook - Wilson, Sarah, 1974- (Clarkson Potter/Publishers, 2015)
You want to give up the sugar-- but you want to keep the breakfasts, smoothies, and treats you love. Wilson shares her repertoire of go-to dishes that will help you make living sugar-free sustainable-- and delicious.